Phenomenology Of Teenagers Playing Online Gambling Higgs Domino Island In Sungai Padang Hamlet, Koto Gasib District, Siak Regency - yuda Tama; Tessa Shasrini Shasrini (Journal Of Social Science (JoSS), 2023)
This study aims to find out what exactly is the motive that arises from the phenomenology of adolescents who play online gambling Higgs Domono Isalnd in Sungai Padang Hamlet, Koto Gasib District, Siak Regency where currently many teenagers in the hamlet play this online gambling game even though whose name gambling is clearly prohibited in Indonesia and prohibited in Islamic law because it will only have a negative impact, in this study to be able to find out the motives of researchers using Alfred Schutz's theory. And this study uses descriptive research with a qualitative approach aiming to make direct observations in the field to obtain the necessary data. And this study involved 6 informants who actively played online gambling Higgs Domino Island. And from the results of the study it can be seen that the motives that emerge from this phenomenology are past motives (Because motives) such as the experience of seeing friends play and seeing advertisements, then the second motive are future motives (in order to motive) such as entertainment, finance and friendship environment.